EVALUATION OF COMPUTATIONAL PRODUCTIVITY SCALING FOR PARALLEL IMPLEMENTATION OF LARGE EDDY SIMULAION METHOD - Шквар, Є. (Proceedings of National Aviation University (archive), 2012)
For one of calculation-intensive methods of fluid-dynamics problems, which intensively becomes populardue to increasing power of high-performance computing and reducing the cost of computations, namely theLarge Eddy Simulation (LES) method, the structuring on elements and analysis of their ability to multithreadedparallelization have been performed. The advantages of explicit finite difference schemes incomparison with the implicit on the base of the criterion of efficiency in parallel algorithms andprogramming methods LES have been justified. A comparative analysis demonstrated that the mostdemanding of computer resources utilization is the solution of Poisson differential equations and the firstphase of the method of splitting by physical processes. The obtained results can be effectively used for bothjustification of the choice of calculation methodology and optimization of parallel algorithms for solving awide range of resource-demanding problems in different spheres of fluid-dynamics.